Study of the antioxidant capacities and inhibitory effect of Cleome arabica L on α-amylase - SEGLAB , Fatiha; Yousfi Mouhamed (Université de Laghouat , Bibliothèque centrale, 2020)
Cleome arabica L belongs to the family of Capparaceae. It has attracted a great deal of attention in recent years for its pharmaceutical potentials due to its antioxidant, antihypercholisterolemic, anti-cancer and chemoprotective activities for the treatment of a number of diseases. The main aim of this study was to evaluate the á-amylase inhibitory and antioxidant activities of extracts from Cleome arabica collected on two seasons (January and November,2015, December 2016 and May 2017) in the town of Laghouat, steppe region of Algeria. The additional purpose of the study was to investigate a new natural inhibition of á-amylase using an in vitro model, as well as to find a natural anti-diabetic compound from the plant. The extracts were prepared with two solvent systems: hydroalcoholic (80/20) and acetonic solvent (70/30) systems. The crude hydromethanolic extracts were obtained by maceration in (M/W) (80/20) of eleven Cleome arabica leaves samples from November and January, the total phenolic content in the ethyl acetate fraction ranged between 0.341±0.009 and 0.751±0.018mg GAE/g dry matter and 0.170±0.0005 to 0.490±0.008mgGAE/g for the dichloromethane fraction, and between 0.060 ±0.004 to 0.453± 0.020mgGAE/g for the n-hexane fraction. The amount of flavonoids content in the ethyl acetate fraction ranged from 0.172±0.001 to 0.682±0.003 mg QE/g. The results of the condensed tannins in the ethyl acetate fraction varied between 0.172±0.008 to 0.332±0.007 mg CE/g, we conclude that the ethyl acetate is the best extractor of flavonoids and the condensed tannins belonging only to this fraction. The total phenolics of ultrasound assisted extraction of hydro-Methanolic (80/20) and hydro-Acetonic (70/30) extracts present in different solvents of C.arabica parts (leaves, pods ,seeds, stems and roots) vary from 2.87 to 107.21 mgGAE/100g at the beginning of maturity stage (December) and rang between 3,981 to 99.6 mgGAE/100g at the end of maturity stage (May), the ethyl acetate fraction proved to be richer in total phenolics and flavonoids (107.21mgGAE/100g and 88.50 mgQE/100g) respectively in hydro-acetonic extract of leaves in the beginning of maturity stage , No remarkable differences were found in both extraction systems and methods, antioxidant activity was assessed using different tests: ferric reducing ability power (FRAP, DPPH,CUPRAC,ABTS and Phosphomolybdenum complex methods . The highest antioxidant capacities of Cleome arabica leaves extracts for November and January were detected by ABTS with EC50 values ranged from (0.009 to 0.013 mg/ml). PM-complex, ABTS,CUPRAC and FRAP were strongly positively correlated with each other , the EC50 values of hydro methanolic and acetonic extract in different fractions of Cleome arabica parts were approximately ranged between 0.0086 and 0.5 mg/ml for December and May months evaluated with DPPH ,antidiabetic activity was investigated by á-amylase inhibition tests , The hydro- acetonic extract showed the best activity against á-amylase compared with hydro-methanolic extract . The IC50 values were very low in ethyl acetate in both pods and seeds organ cited there IC50 are (IC50= 0.11mg/ml), (IC50 = 1.03mg/ml), respectively . Similar case with n-hexane fractions with (IC50 = 0.6 mg/ml, EC50 = 1.08 mg/ml ) for stems and seeds respectively in the beginning of maturity stage . This study is the first report on potential inhibition of these plant extracts on the digestive enzyme, á-amylase. The results indicate that Cleome arabica of Algeria is a powerful natural antioxidant and that it could also provide natural biologically active agents to be used in the management of diabetes.